A formaldehyde-free binder for engineered wood products. Issue 1 (March 2014) - Sivasubramanian, Shivshankar; Jafferji, Khozema; Schmidt, Daniel F.; Reynaud, Emmanuelle
Abstract : This study aims at evaluating an alternative to petroleum-derived thermosets for engineered wood products from the standpoint of mechanical performance. The chosen system consists of epoxidized linseed oil cross-linked with a polyamine compound; the constituents are chosen for their minimal toxicity profiles. In a first step, the authors report on the optimization of network composition, as assessed by mechanical property measurements and supported by thermal analysis. For a 1:1·8 epoxy to amine hydrogen ratio, the cross-linked network exhibits a maximum Shore D hardness of 81 and a maximum glass transition temperature of 45°C; at the same time, the presence of a thin, soft layer of material is observed on the underside of samples of these networks. To remedy this issue, two families of nanoparticles (montmorillonite clay and hydrotalcite) are added to the bioepoxy formulation; it is found that only the latter family enables reinforcement and enhances homogeneity. In follow-up experiments, wood composites are manufactured with the optimized bioepoxy formulation (with and without hydrotalcite nanoparticles) and are found to possess a higher main relaxation temperature (65°C) and properties on par with commercially available engineered wood products.